Human intracranial recordings and cognitive neuroscience.[article]. - Mukamel, Roy
The ultimate goal of neuroscience research is to understand the operating mechanism of the human brain and to exploit this understanding to devise methods for repair when it malfunctions. A key feature of this operating mechanism is electrical activity of single brain cells and cell assemblies. For obvious ethical reasons, scientists rely mostly on animal research in the study of such signals. Research in humans is often limited to electrical signals that can be recorded at the scalp or to surrogates of electrical activity, namely magnetic source imaging and measures of regional blood flow and metabolism. Invasive brain recordings performed in patients during various clinical procedures provide a unique opportunity to record high-resolution signals in vivo from the human brain-data that are otherwise unavailable. Of special value are the rare opportunities to record in awake humans the activity of single brain cells and small cellular assemblies. These recordings provide a unique view on aspects of human cognition that are impossible to study in animals, including language, imagery, episodic memory, volition, and even consciousness. In the current review we discuss the unique contribution of invasive recordings from patients to the field of cognitive neuroscience. - (from the authors)